The Incarnation of Christ is A Great Mystery in Righteousness (Study Exegesis in Timothy 3:16) - Dwiraharjo, Susanto (Scriptura Indonesia, 2024)
Various perspectives on the doctrine of Christology are not only widespread, but also deeply ingrained in the fabric of theological discourse. These perspectives have influenced the faith of believers. This research explores the truth of Christology based on what the Bible says. The method used is explanation, which will reveal the original meaning of the verses and seek to understand their relevance to contemporary issues. Consequently, it can be understood that Christ is God who became man to carry out His redemptive work.